Phylogenetic Footprint Analysis of IGF2 in Extant Mammals - Weidman, Jennifer R.; Murphy, Susan K.; Nolan, Catherine M.; Dietrich, Fred S.; Jirtle, Randy L. (Genome Research, 2004)
Genomic imprinting results in monoallelic gene transcription that is directed by cis-acting regulatory elements epigenetically marked in a parent-of-origin-dependent manner. We performed phylogenetic sequence and epigenetic comparisons of IGF2 between the nonimprinted platypus (Ornithorhynchus anatinus) and imprinted opossum (Didelphis virginiana), mouse (Mus musculus), and human (Homo sapiens) to determine if their divergent imprint status would reflect differences in the conservation of genomic elements important in the regulation of imprinting. We report herein that IGF2 imprinting does not correlate evolutionarily with differential intragenic methylation, nor is it associated with motif 13, a reported IGF2-specific “imprint signature” located in the coding region. Instead, IGF2 imprinting is strongly associated with both the lack of short interspersed transposable elements (SINEs) and an intragenic conserved inverted repeat that contains candidate CTCF-binding sites, a role not previously ascribed to this particular sequence element. Our results are the first to demonstrate that comparative footprint analysis of species from evolutionarily distant mammalian clades, and exhibiting divergent imprint status is a powerful bioinformatics-based approach for identifying cis-acting elements potentially involved not only in the origins of genomic imprinting, but also in its maintenance in humans.